Kajian Hydrocooling dan Tempat Penyimpanan untuk Mempertahankan Kualitas Cabai Gendot (Capsicum annum var. Abbreviata) - Dewi, Sukuriyati Suliso (Universitas Muhammadiyah Yogyakarta, 2015)
The purpose of this study was to understand the effect of hydrocooling and storage on the quality and shelf life of gendot Chili. This study was conducted in Post Harvest Laboratory and Chemistry, Faculty of Agriculture, Universitas Muhammadiyah Yogyakarta. Research was arranged in a completely randomized design (CRD). The first factor is Hydrocooling treatment which consists with and without hydrocooling. The second factor is storage which consist three kind of storage, there are ice box, cooler, and refrigerator. Chili was kept in the storage for 20 days. Parameters of observation were weight losses, damage percentage, fruit hardness, moisture content, vitamin C, reducing sugar, microbiological and organoleptic test. Result showed that hydrocooling treatment was not signicantly effect to the quality of chili. However, hydrocooling treatment is affecting to moisture, Vitamin C, and reducing sugar contents. Storage rooms was not significantly effecting to the quality of chili. There is any interactions between hydrocooling treatment and storage on moisture content, Vitamin C contents, and reducing sugar content.